Economic Cost and Quality of Life of Family Caregivers of Schizophrenic Patients Attending Psychiatric Hospitals in Ghana - Opoku-Boateng, Y.N.; Kretchy, I.A.; Aryeetey, G.C.; Dwomoh, D.; Decker, S.; Agyemang, S.A.; Tozan, Y.; Aikins, M.; Nonvignon, J. (BMC Health Services Research, 2017)
Background Low and middle income countries face many challenges in meeting their populations’ mental health care needs. Though family caregiving is crucial to the management of severe mental health disabilities, such as schizophrenia, the economic costs borne by family caregivers often go unnoticed. In this study, we estimated the household economic costs of schizophrenia and quality of life of family caregivers in Ghana. Methods We used a cost of illness analysis approach. Quality of life (QoL) was assessed using the abridged WHO Quality of Life (WHOQOL-BREF) tool. Cross-sectional data were collected from 442 caregivers of patients diagnosed with schizophrenia at least six months prior to the study and who received consultation in any of the three psychiatric hospitals in Ghana. Economic costs were categorized as direct costs (including medical and non-medical costs of seeking care), indirect costs (productivity losses to caregivers) and intangible costs (non-monetary costs such as stigma and pain). Direct costs included costs of medical supplies, consultations, and travel. Indirect costs were estimated as value of productive time lost (in hours) to primary caregivers. Intangible costs were assessed using the Zarit Burden Interview (ZBI). We employed multiple regression models to assess the covariates of costs, caregiver burden, and QoL. Results Total monthly cost to caregivers was US$ 273.28, on average. Key drivers of direct costs were medications (50%) and transportation (27%). Direct costs per caregiver represented 31% of the reported monthly earnings. Mean caregiver burden (measured by the ZBI) was 16.95 on a scale of 0–48, with 49% of caregivers reporting high burden. Mean QoL of caregivers was 28.2 (range: 19.6–34.8) out of 100. Better educated caregivers reported lower indirect costs and better QoL. Caregivers with higher severity of depression, anxiety and stress reported higher caregiver burden and lower QoL. Males reported better QoL. Conclusions These findings highlight the high household burden of caregiving for people living with schizophrenia in low income settings. Results underscore the need for policies and programs to support caregivers.
Keywords: Caregiving; Economic Burden; Ghana; Quality Of Life; Schizophrenia